Au Clair de la Terre. Mon œil extraterrestre - Elsa De Smet (Images Re-Vues)
From the 17th century, astronomy has been defined as a science of observation, but it stayed nevertheless attached to the field of assumption. Indeed, scholarly literature at the time did not hesitate to put imagination at the very heart of its functioning, by having recourse to the story of a mental travel as a mean to grasp the interstellar world. The eye of the reader is thus projected in literary fiction and will find in the image at the middle of the 19th century a new tool in favouring communication around scholarly astronomy and its learning through enjoyment. Creed of the century, the idea that “you have to see to know” set up a new field of fiction, now visual, at the very center of the most rigorous demonstrations. The reign of spectacle and extraordinary adventures of the second half of the 19th century, which revealed the seduction’s capacity of scientific imagery in popular culture, is undoubtedly partly responsible of that. What is more, from this collaboration between fiction and astronomy emerged esthetical mutations where the coalescence between science and style becomes the necessary condition and starting point for new plastic questionings.